A PENGEMBANGAN DESAIN PERMAINAN BERBASIS ADVENTURE EDUCATION DALAM KEMAMPUAN MOTORIK KELAS III SEKOLAH DASAR - Krisno, Siska; Ardiyanto, Asep; Wakhyudin, Husni (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2025)
The background that drives this research is the low motor skills of students and the lack of innovation in learning Physical Education at Pagejugan 03 State Elementary School. The Solution to these problems is the development of Adventure Education game design in the motor skills of grade III elementary school. The method used was Research and Development (R&D) with the ADDIE model. The research subjects were 29 third-grade students with data collected through observation, interviews, and questionnaires and analyzed qualitatively and quantitatively. The result of the analysis will prove the validity of the developed product. The result of this study are the development of Adventure Education-based game design in the motor skills of grade III elementary school, this game design is validated by experts consisting of two experts, namely game/motion experts and elementary learning experts. The result of the validation of game/movement experts received a score of 97,14% with the criteria “Very Feasible” and the result of the validation of elementary learning experts received a score of 97,89% with the criteria “Very Feasible”. Meanwhile, the results of practicality were obtained from observation questionnaires and teacher questionnaires. The result of the Class teacher questionnaire scored 100% with the criteria “Very Practical” and the PJOK teacher questionnaire scored 100% with the criteria “Very Practical”. While at the stage the result of the students’ questionnaire to determine the acceptance of the game design received a score of 99,54% with the criteria “Very Feasible”. Based on the result of this study, it can be concluded that the development of Adventure Education-based game design in grade III motor skills is valid, practical and acceptable to students so that it is feasible to use in elementary schools.